Do you perceive yourself? Somatics, fascia and movement: an experience report (Research, Society and Development, 2022)
This study aimed to describe the lived perceptions of professionals residing in a Multidisciplinary Health Team about their experiences in a movement practice with a fascial and somatic approach. Experience report study carried out in a public institution of higher education in the State of Piauí, with 15 (fifteen) health professionals, during the months of September and October 2021, with a total of 4 (four) meetings lasting approximately 1 (one) hour each. The practices started with a summary assessment, image stimuli followed by audio recording of the first perceptions, practice of the Vectors and Movement – An Approach to Fascia repertoire, revisitation of the image stimuli and audio recording of the final perceptions. Words referring to states of lightness, relaxation, tranquility, gains in concentration, attention or body perception were reported by the participants after the final imagery stimuli. It was also possible to observe gains in proprioception, symmetry, stability, mobility, coordination, posture and decreased pain and discomfort. This study concludes that movement practices with a fascial and somatic approach can prove to be a valid tool for evaluation, prevention, and intervention in health processes.